PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VII1 SMP NEGERI 8 PEKANBARU - Bita Anggriani; Titi Solfitri; Armis Armis (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is classroom action research that aims to improve learning process and to increase mathematics achievement with applied the learning model of Problem Based Learning. The subject of this research were 37 students of class VII1 SMPN 8 Pekanbaru in academic years 2017/2018, consist of 17 boys and 20 girls. The research consist of two cycles, each cycle has four stages, which are planning, implementation, observation, and reflection. The instruments of data collection in this research were observation sheets and students Mathematic tests. The observation sheets were analyzed in qualitative desciptive, while the students’ Mathematic tests were analyzed in quantitative descriptive. The qualitative descriptive showed an improvement of learning process prior to the action on the first and second cycle. Most of students were very confidenced and actived in learning process, such as while they were finished mathemathic’s problems that given, presenting the result of problems and giving the conclusion of learning. Number of students that reach Minimum Mastery Criteria increase from basic score to first test I and II. The results of this research showed an increasing number of students learning mathematics about knowledge of the basic score (29,73%) to the first test (51,35%) to the second test II (72,97%). For the skills of basic score the first test (35,14%) to the second test (54,05%), Results of this research indicates that appication of the learning model of Problem Based Learning can improve learning process and increase mathematics achievement from the students at class VII1 SMPN 8 Pekanbaru in academic years 2017/2018 for the subject matter the set.Key Words : Mathematics Achievement, Problem Based Learning, Class Action Research